The glow : an inspiring guide to stylish motherhood - Gaynor, Violet (Stewart, Tabori & Chang, 2014)
"The Glow provides a rare glimpse into the world of fashionable mothers at home, capturing tender moments between them and their young ones and sharing their inspiration, insights and a few of their favorite things. Violet Gaynor and Kelly Stuart, creators of the popular website TheGlow.com, bring their unique vision of motherhood to the page through gorgeous photographs and intimate interviews with tastemaker moms that follow the path from pregnancy to parenthood with wry wit, charming advice, and a deep understanding of the affectionate relationship between parent and child. Inside these pages, the stylish moms reveal everything from personal style to home decor, recipes, fitness, beauty, marriage, and more." --